Modulation of the symbionts light environment in hospite in scleractinian corals - Galindo-Martínez, Claudia Tatiana; Chaparro, Arelys; Enríquez, Susana; Iglesias-Prieto, Roberto (Frontiers in Marine Science, 2022)
The upregulation of animal chromoproteins (CPs) during thermal stress produces “colorful” bleached corals that facilitate coral recovery after bleaching. In situ measurements indicate that animal CPs present in coral tissues reduce the elevated internal light environment of the remaining symbionts in bleached or low-pigmented stressed corals. However, there is still a lack of understanding regarding the extent to which animal CPs contribute to modifying the internal light environment of the symbionts in hospite. In this study, we evaluate the effect of three animal CPs on the optical properties of the coral tissue and their internal light environment using a numerical model. The model allows estimations of the absorbance spectra of corals as a function of changes in symbiont and animal pigmentation, as well as descriptions of the light environment in hospite of the symbionts. These descriptions were derived from the quantification of the contribution of each pigment component to light absorption, together with the contribution of the coral skeleton’s reflectance. Simulations indicate that animal CPs upregulation modifies the spectral distribution and the intensity of the internal light field. Animal CPs can reduce up to 11% of the light intensity in hospite when present individually, and up to 24% when present in combination. Such reduction may play a critical role in preventing the full development of the bleached phenotype when irradiance rises to excessive levels at low coral pigmentation, facilitating coral recovery and symbiont tissue re-colonization after bleaching. Accordingly, coral’s CPs components need to also be considered when selecting coral species for future restoration efforts.